Medical education in clerkship: From here and out - Prananjaya, Bintang Arroyantri; Syulthoni, Zain Budi; Maritska, Ziske; Nudhar, Lathifah; Aini, Syarifah; Suryani, Puji Rizki; Ikhsan, Diyaz Syauki (Universitas Muhammadiyah Surabaya, 2024)
The COVID-19 pandemic has changed many things in the medical education system. This change requires adaptation and modification from education providers, teachers, and students. A virtual learning system has been implemented instead of a face-to-face learning system. However, this makes several challenges and issues that must be considered. Virtual learning is considered less attractive and interactive and not effective in teaching clinical skills. For student clerks, the reduced time to undergo education in the hospital leads to fewer case exposures. Another problem is the facilities and infrastructure. Several ways to solve this problem have been implemented while minimizing risk and taking strict precautions. Some institutions modify and innovate to maximize the effectiveness of learning activities. In addition to technical and effectiveness issues, changes in the education system also have an impact on the mental health of medical students, therefore it is important for institutions to be sensitive to changes and risks to students' mental health during the pandemic.